X-change symposium: status and future of modern radiation oncology—from technology to biology - Corradini, Stefanie; Niyazi, Maximilian; Verellen, Dirk; Valentini, Vincenzo; Walsh, Seán; Grosu, Anca L.; Lauber, Kirsten; Giaccia, Amato; Unger, Kristian; Debus, Jürgen; Pieters, Bradley R.; Guckenberger, Matthias; et al. (Radiation Oncology, 2021)
Future radiation oncology encompasses a broad spectrum of topics ranging from modern clinical trial design to treatment and imaging technology and biology. In more detail, the application of hybrid MRI devices in modern image-guided radiotherapy; the emerging field of radiomics; the role of molecular imaging using positron emission tomography and its integration into clinical routine; radiation biology with its future perspectives, the role of molecular signatures in prognostic modelling; as well as special treatment modalities such as brachytherapy or proton beam therapy are areas of rapid development. More clinically, radiation oncology will certainly find an important role in the management of oligometastasis. The treatment spectrum will also be widened by the rational integration of modern systemic targeted or immune therapies into multimodal treatment strategies. All these developments will require a concise rethinking of clinical trial design. This article reviews the current status and the potential developments in the field of radiation oncology as discussed by a panel of European and international experts sharing their vision during the “X-Change” symposium, held in July 2019 in Munich (Germany).
CRIS-Team Scopus Importer:2025-10-13